Flood vulnerability index to aid decision making - Geeta Aggarwal; Harita Ahuja; Sunita Narang; Seema Aggarwal (Universitas Ahmad Dahlan, 2024)
Floods damage ecosystem of the affected area resulting in destruction, loss of asset and life. The paper proposes a novel k-FVI, (k stands for Kerala and FVI for flood vulnerability index) to aid the decision makers reduce flood vulnerability of 14 districts of Kerala. Instead of usual classification of flood vulnerability indicators under exposure (?), sensitivity (?), and adaptive capacity (?ℂ), k-FVI proposes that, indicators reflecting ? and preparedness (ℙ)govern pre-flood vulnerability, whereas those of ? and rehabilitation (ℝ) affects post-flood vulnerability. The division of ?ℂ indicator into ℙ and ℝ indicators and clubbing them into pre-flood and post-flood vulnerability respectively results into reduced errors. The importance of high dimensional flood indicators is realized by measuring the entropy of affected areas. Use of technique for order preference by similarity to ideal solution (TOPSIS) and entropy-based weights to score flood affected area results in formulating robust k-FVI. The paper also compares k-FVI with existing FVIs in literature. It uses data of 2018 Kerala floods and assesses the flood vulnerability of its 14 districts. The results prove that k-FVI is an effective flood vulnerability score estimator. Variant of k-FVI can be used to obtain vulnerability for any other flood prone areas.